1990
DOI: 10.1002/aja.1001890102
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar structure and synthetic activity during meiotic prophase and spermiogenesis in the rat

Abstract: The ultrastructure of nucleoli was examined in developing rat spermatocytes and spermatids, with the help of serial sections. In addition, the radioautographic reaction of nucleoli as examined in rats sacrificed 1 hr after intratesticular injection of 3H(5')-uridine and taken as an index of the rate of synthesis of ribosomal RNA (rRNA). Primary spermatocytes from preleptotene to zygotene have small nucleoli typically composed of fibrillar centers, a fibrillar component, and a granular component, within which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The nubecula is composed of loosely organized threads organized into a 560-nm spheroid ). An ultrastructure study of nucleoli in rat spermatocytes and spermatids was reported by Schultz and Leblond (1990). During early and mid pachytene, nucleoli enlarge nine times their initial size and then undergo condensation in late pachytene spermatocytes.…”
mentioning
confidence: 98%
“…The nubecula is composed of loosely organized threads organized into a 560-nm spheroid ). An ultrastructure study of nucleoli in rat spermatocytes and spermatids was reported by Schultz and Leblond (1990). During early and mid pachytene, nucleoli enlarge nine times their initial size and then undergo condensation in late pachytene spermatocytes.…”
mentioning
confidence: 98%
“…Apparently, its nucleolus no longer contains DNA at this point and shows a highly compacted, fibrillar morphology [2,3]. As the nucleolus is eliminated during spermiogenesis [4][5][6], the spermatozoa do not have nucleoli. After fertilization, this maternally derived, transcriptionally inactive fibrillar nucleolus appears in both male and female pronuclei and in the embryonic nuclei of each interphase until the 4-or 8-cell stage; that is, it is present until the time at which zygotic RNA polymerase I activity is fully established [7].…”
mentioning
confidence: 99%
“…After embedding in Epon, random and serial sections were prepared as indicated in the accompanying article (Schultz and Leblond, 1990). 7.4 were also obtained (Schultz and Leblond, 1990). In addition, a histochemical study of the coiled body was carried out, using phosphotungstic acid for the detection of protein by the method of Silverman and Glick (1969), and using ribonuclease-bound gold for the detection of RNA by the method of Bendayan (1981a,b).…”
Section: Methodsmentioning
confidence: 99%
“…After embedding in Epon, random and serial sections were prepared as indicated in the accompanying article (Schultz and Leblond, 1990). 7.4 were also obtained (Schultz and Leblond, 1990).…”
Section: Methodsmentioning
confidence: 99%